2007
DOI: 10.1007/s00415-006-0460-0
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in dyslexic and non-dyslexic children

Abstract: Postural control relies to visual-motion processing (afferent or efferent) and this is thought to be deficient in dyslexics. There is a controversy between clinic and fundamental studies as to the presence of posture abnormalities in dyslexics. To explore further this issue, this study examines posture stability in quite stance in 13 dyslexics (mean age: 13.5 years) and in 13 non-dyslexics (mean age: 13 years). Experiment 1 shows that, similarly to adults and elderly, all children (dyslexics and non-dyslexics)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
5
34
0
Order By: Relevance
“…Despite the conflict with the physical distance, convergence of the eyes resulted in an improvement in postural stability. This stabilizing effect of proximity is present in children 3 and in the elderly. 2 Bucci et al showed that children with a vergence deficit who suffered from vertigo still presented this stabilizing effect of proximity with respect to postural control even though they were less stable than control children for conditions at near and far distances.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Despite the conflict with the physical distance, convergence of the eyes resulted in an improvement in postural stability. This stabilizing effect of proximity is present in children 3 and in the elderly. 2 Bucci et al showed that children with a vergence deficit who suffered from vertigo still presented this stabilizing effect of proximity with respect to postural control even though they were less stable than control children for conditions at near and far distances.…”
Section: Discussionmentioning
confidence: 90%
“…As mentioned above, Kapoula and Bucci confirmed that for dyslexic children, active vergence eye movements exert a stabilizing effect on posture that has not been observed in non-dyslexic control children. 3 They attributed these results to dyslexic children's greater visual attentional involvement, as well as to the mobilization of attentional resources together with the execution of eye movements. Because dyslexic children also have attentional difficulties, active vergence movements could help to focus their attention by shifting between distal and proximal targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kapoula and Bucci [1] measured postural control in 13 year-old dyslexic adolescents during both closed and opened eye conditions while they were instructed to fixate a target at distances of 25 cm and 150 cm. Dyslexics were more unstable during such fixation tasks regardless of the distance at which the target was placed, be it proximal or distal.…”
Section: Introductionmentioning
confidence: 99%